Asymmetric Suzuki-Miyaura coupling of heterocycles via Rhodium-catalysed allylic arylation of racemates - Schäfer, P; Palacin, T; Sidera Portela, M; Fletcher, S (Springer Nature, 2017)
Using asymmetric catalysis to simultaneously form carbon-carbon bonds and generate single isomer products is strategically important. Suzuki-Miyaura cross-coupling is widely used in the academic and industrial sectors to synthesize drugs, agrochemicals and biologically active and advanced materials. However, widely applicable enantioselective Suzuki-Miyaura variations to provide 3D molecules remain elusive. Here we report a rhodium-catalyzed asymmetric Suzuki-Miyaura reaction with important partners including aryls, vinyls, heteroaromatics and heterocycles. The method can be used to couple two heterocyclic species so the highly enantioenriched products have a wide array of cores. We show that pyridine boronic acids are unsuitable, but they can be halogen-modified at the 2-position to undergo reaction, and this halogen can then be removed or used to facilitate further reactions. The method is used to synthesize isoanabasine, preclamol, and niraparib – an anticancer agent in several clinical trials. We anticipate this method will be a useful tool in drug synthesis and discovery. A correction to this article is available at: https://doi.org/10.1038/ncomms16216